Antibacterial effect of aqueous extract of Syzygium Aromaticum and floxacin against gram negative and positive bacteria: an in-vitro study - Al-Oudah, GA; Hindi, NKK; Al-Shalah, LAM; Jalil Ewadh, RM; Mohammed, SM (Plant Science Today, 2025)
Syzygium aromaticum is an antibacterial activity against various pathogenic microorganisms. A broad range of anti-disease activities estimate its potential therapeutic uses in treating numerous infectious disorders. The study aims to understand better how Syzygium aromaticum extract inhibits human pathogenic bacteria and demonstrate how the extract works to prevent the formation of bacterial biofilms and adhesion. The antibacterial action of the aqueous extract of Syzygium aromaticum was evaluated by using disc diffusion and the assay Agar-well diffusion. Its efficacy was compared with the antibiotic and determined. Additionally, tests on adherence and biofilm formation were conducted. All bacteria isolated from gram-negative (G -ve) and gram-positive (G +ve) bacteria were sensitive to Syzygium aromaticum extract and the range of inhibition zone (20 to 28) mm. Most isolated bacteria were sensitive to floxacin. Most bacterial isolates of Gram-negative bacteria exhibited Moderate adherence and biofilm activity to these extracts. Some bacteria isolates exhibited high adherence and biofilm activity to aquatic extracts of Syzygium aromaticum. The studys' findings were that the extracts from Syzygium aromaticum were highly effective against a variety of G-positive and G-negative isolated clinically, suggesting that they are superior to antibiotics sold in stores. Apart from strong resistance to adhesion and biofilm development.